Blogging among the government servant : factors that influence them / Laviana Albert Anchah & Mulyani Nong Che’ - Albert Anchah, Laviana; Nong Che’, Mulyani (2009)
The purpose of this research is to study on factors that influence government servant blogging. There are certain factors that influence them to create or using blog such as gender, position and the reason of using blogs. Surveys were distributed to 100 employees in four (4) government department in Kuching, 72 were returned and found to be valid for analysis. The result of findings show that all the three factors are influences them to blogging. Gender factor has a strong positive relationship with the reason they are blogging in their department followed by position factor and reason of using blogs factor that has a moderate correlation.